Conceptual Design Of Photothermal Electrochemical Water Resonant Electrolysis - Gan, Leong Ming (2010)

(untitled)
Since there is very limited natural hydrogen source, various methodologies had been proposed to extract hydrogen gas from both renewable and non-renewable resources. Among all, solar fuel or solar hydrogen fuel shows the most fascinating prospect to replace the conventional energy scheme. A detail comparison on both fossil based and solar based hydrogen generation method is reviewed. Although photothermal electrochemical water splitting technique shows highest preliminary efficiency, it is not practical due to cost, material and area requirement. Based on CST dish/Stirling technology, non-hybrid photothermal electrochemical process is approached and compared. By yielding higher hydrogen output without decreasing the water electrolysis efficiency, resonant electrolysis is proposed to integrate with the named solar harvesting technique. Detail discussion is make for the proposed operating system design and the effectiveness of harvest mono-atomic hydrogen fuel through theoretical analysis using both chemical bond and enthalpy of formation technique. The theoretical result shows that the mono-atomic hydrogen contain 3.83 times of energy compare to diatomic hydrogen gas. Last but not least, a conceptual design of resonant electrolysis and working principle is also summarised.